Local Wisdom Integration in Digital Science and Social Studies Teaching Materials: An ADDIE-Based Flipbook Development for Fifth-Grade Elementary Learners - Fira Astuti Sukardi; Yusdin B M Gagaramusu; Surahman Wilade; Zulnuraini Zulnuraini; Danti Indriastuti Purnamasari (Journal of Innovation and Research in Primary Education, 2026)
Integrated science and social studies (IPAS) instruction in Indonesian elementary schools frequently remains textbook-centered and disconnected from students' local contexts, limiting engagement and conceptual understanding. The integration of local wisdom into digital teaching materials represents a promising yet underexplored approach to addressing this gap, particularly within the framework of the Merdeka Curriculum. This study employed a Research and Development (R&D) design guided by the ADDIE model to develop a local wisdom-based IPAS flipbook for fifth-grade students at SDN 10 Palu, Central Sulawesi, Indonesia. The participants comprised 23 students, one classroom teacher, and one media expert. Data were collected through media expert validation sheets (22 items; CVR = 0.99) and student response questionnaires (24 items; Cronbach's α = 0.87), both using a four-point Likert scale. The developed flipbook — titled Petualangan di Lembah Palu — integrates endemic Central Sulawesi flora and fauna with culturally grounded narratives. Expert validation yielded a score of 92.9% (very valid), and student practicality responses reached 98.4% (very practical) across dimensions of visual attractiveness, ease of use, content comprehension, and learning motivation. These results indicate that a systematically designed, culturally contextualized digital flipbook can achieve high feasibility standards for elementary IPAS learning. The study offers a replicable model for developing locally grounded digital instructional materials aligned with the Merdeka Curriculum. Future research should examine the flipbook's effectiveness on learning outcomes through experimental designs and extend implementation to diverse school contexts.